ФАЛСАФА ФАНИНИНГ ДОЛЗАРБ МУАММОЛАРИ (Scientific journal of the Fergana State University, 2023)
This article clears a relevant problem of philosophical science, their sources, contents, reason and result and ways of their resolution.